The effect of socio-economic challenges of youth unemployment on the economy of South Africa, a specific references to Limpopo Province - Choenyane, Letlema Leonard (My University, 2022)
This study investigated the socio-economic effects of the youth unemployment on the economy of Limpopo Province. Youth unemployment is rife in the province whereby drugs, alcohol abuse, HIV/AIDS, and crime affect young people. A great number of these young people are unskilled or semi-skilled and are therefore not able to create jobs for themselves; they rely on government for job creation. Thus, a research was conducted in Capricorn District of Limpopo Province, wherein participants were drawn from two municipalities. The two municipalities that were identified for the study were Polokwane and Lepelle-Nkumpi. These municipalities were identified due to the number of active youth programmes that they conduct. A total of 54 individuals participated in the study. They included the municipality officials and the young people. A quantitative research approach was used to collect and analyse data. A Likert scale was used as a research instrument to collect data. Self-administered questionnaires were distributed to the selected participants. Thus, the Statistical Package for the Social Sciences (SPSS) version 25 was used to analyse data. The major finding in the research was that unemployment affected all the youth across the entire education spectrum. The study therefore recommended changes in the education system, and rigorous programmes on entrepreneurship.
Thesis (MBA. (Business Administration)) -- University of Limpopo, 2022
Keywords: Youth; Unemployment; Socio economic; Entrepreneurship; Programmes; Economics -- Sociological aspects; Economic rights; Unemployment -- South Africa -- Limpopo